Chicken Skin Antifreeze Peptides: Ice Crystal Inhibition Activity and Quality Control of Chicken Mince during Freeze-Thaw Cycles - CAI Dongna, DU Shuang, JIANG Wenting, BU Shuai, YANG Ao, WANG Shaoyun, CHEN Xu, CAI Xixi (Shipin Kexue)
This study assessed the effects of antifreeze peptides (CsAFPs) produced by enzymatical hydrolysis of chicken skin on chicken mince stability. CsAFPs, 85.88% of which were short peptides (180–3 000 Da), showed high hydrophilicity and strong thermal hysteresis activity and ice recrystallization inhibition activity, reducing the ice crystal content by (26.03 ± 0.40)% and raising the glass transition temperature by 7.3 ℃. The flavor of CsAFPs was well coordinated with that of chicken mince and the addition of 2% CsAFPs enhanced the water-holding capacity of chicken mince without color change. After four freeze-thaw cycles, mince added with 2% CsAFPs showed less reductions in water-holding capacity, elasticity, and resilience than did the control group. Ultraviolet (UV) absorption and Fourier transform infrared spectroscopy (FTIR) indicated that CsAFPs could prevent the aggregation and denaturation of proteins under freezing stress. After freeze-thaw cycles, the r value of myofibrillar protein in the mince with 2% added CsAFPs was higher than the control group without CsAFPs. This study contributes to a better understanding of the protective mechanisms of CsAFPs in frozen meat and highlights that CsAFPs are promising novel low-sweetness and low-calorie cryoprotectants for meat products.